Two Anniversaries of Challenge and Change - Schafran, Lynn Hecht (Columbia Journal of Gender and Law, 2000)
The tenth anniversary of the Columbia Journal of Gender and Law coincides with the twentieth anniversary of the National Judicial Education Program to Promote Equality for Women and Men in the Courts, of which I have been Director since 1981. While a decade or two is a nanosecond in historical time, in the context of women’s legal history, these decades from 1980 to 2000 loom large because they have produced such dramatic and positive change. When the National Judicial Education Program (NJEP) began its work in 1980, judges’ and attorneys’ gender bias was an invisible problem. Today it is grounds for reversal and sanction. In 1980, knowledgeable judges, lawyers, and journalists told NJEP that judges would never acknowledge that gender bias was a problem in their courts or an appropriate subject for judicial education. At the National Conference on Public Trust and Confidence in the Justice System in May 1999, 500 state chief justices, state court administrators, state bar presidents, and other justice system leaders voted to make implementation of the recommendations of the state task forces on gender, race, and ethnic bias in the courts a priority. Indeed, just the existence of these task forces, established in response to NJEP’s educational programs, testifies to the difference these decades have made.